A method to optimize ship maneuvers for the coordination of hardkill and softkill weapons within a frigate - Blodgett, Dale; Plamondon, Pierrick; Chaib-draa, Brahim; Kropf, Peter; Bossé, Eloi (My University, 2002)
The coordination of anti-air warfare hardkill and softkill weapon systems is an important aspect of command and control for a Frigate. Since the effectiveness of a particular weapon varies depending on the orientation of the Frigate with respect to the threats faced, a key element of the coordination process is to maneuver the Frigate to most effectively use all the weapons available. This paper shows that the environment surrounding the Frigate can be divided into six fundamental sectors for weapon engagement. The method to determine the general effectiveness of each sector for the threats faced is shown. A naïve Bayes method that determines the optimal positioning of the Frigate to most effectively use the hardkill and softkill weapons is presented. Also discussed are the different types of planners that were investigated for planning engagements for the hardkill and softkill weapon systems. Preliminary results comparing and rating these planners are shown, both with and without the recommended maneuvers.
, 2002